Uplink Performance Evaluation of Packet Combining ARQ for MPR Prefix-Assisted DS-CDMA - Dinis, Rui (2018)
Prefix-assisted direct-sequence code-division multiple access (DS-CDMA) is a viable transmission technique for high-data-rate wireless broadband systems, capable of coping with highly dispersive channels at the uplink. Packet combining (PC) ARQ with an iterative block decision feedback equalization (IB-DFE) technique can be used to cope with errors. However, extracting the IB-DFE's packet error rate (PER) for MAC-layer simulations can be time consuming. Most works that model the DS-CDMA behavior with PC ARQ use simplified asymptotic PER models in the study of the system performance, which are not precise for low signal-to-noise ratios and for a low number of mobile terminals (MTs). In this paper, the MAC performance is modeled using a discrete-time Markov chain that relies on a PER model. As an example, this paper describes a PER analytical model for an uncoded prefix-assisted DS-CDMA system with PC ARQ that considers the following inputs: the number of MTs accessing the channel, the MTs' number of transmissions, and the channel realizations for a given bit energy over noise ratio. The results show that the model portrays with better accuracy the simulations' results, compared with an alternative asymptotic model.